ACAT-selective and Nonselective DGAT1 Inhibition: Adrenocortical Effects—A Cross-species Comparison. (October 2013) - Floettmann, Jan Eike; Buckett, Linda K.; Turnbull, Andrew V.; Smith, Tim; Hallberg, Carina; Birch, Alan; Lees, David; Jones, Huw B.
Acyl-coenzyme A: cholesterol O -Acyltransferase (ACAT) and Acyl-coenzyme A: diacylglycerol O -acyltransferase (DGAT) enzymes play important roles in synthesizing neutral lipids, and inhibitors of these enzymes have been investigated as potential treatments for diabetes and other metabolic diseases. Administration of a Acyl-coenzyme A: diacylglycerol O -acyltransferase 1 (DGAT1) inhibitor with very limited cellular selectivity over ACAT resulted in significant adrenocortical degenerative changes in dogs. These changes included macrosteatotic vacuolation associated with adrenocyte cell death in the zonae glomerulosa and fasciculata and minimal to substantial mixed inflammatory cell infiltration and were similar to those described previously for some ACAT inhibitors in dogs. In the mouse, similar but only transient adrenocortical degenerative changes were seen as well as a distinctive nondegenerative reduction in cortical fine vacuolation. In the marmoset, only the distinctive nondegenerative reduction in cortical fine vacuolation was observed, suggesting that the dog, followed by the mouse, is the most sensitive species for cortical degeneration. Biochemical analysis of adrenal cholesterol and cholesteryl ester indicated that the distinctive reduction in cortical fine vacuolation correlated with a significant reduction in cholesteryl ester in the mouse and marmoset, whereas no significant reduction in cholestryl ester, but an increase in free cholesterol was observed in dogs. Administration of a DGAT1 inhibitor with markedly improved selectivity over ACAT to the marmoset and the mouse resulted in no adrenal pathology at exposures sufficient to cause substantial DGAT1 but not ACAT inhibition, thereby implicating ACAT rather than DGAT1 inhibition as the probable cause of the observed adrenal changes. Recognizing that the distinctive nondegenerative reduction in cortical fine vacuolation in the mouse could be used as a histopathological biomarker for an in vivo model of the more severe changes observed in dogs, the mouse has subsequently been used as a model to select DGAT1 inhibitors free of adrenocortical toxicity.